A 5-year evaluation of the emergency contraception enhanced community pharmacy service provided in Wales. Issue 4 (8th August 2019) - Mantzourani, Efi; Hodson, Karen; Evans, Andrew; Alzetani, Sarah; Hayward, Rebecca; Deslandes, Rhian; Hughes, Mary Louise; Holyfield, Gareth; Way, Cheryl
Abstract : Background: Access to emergency contraception (EC) has been a core component of attempts to address high teenage pregnancy rates in Wales. A national service was commissioned in 2011, allowing supply of EC free of charge from community pharmacies (CPs). This study investigated 5 years of the EC service, to describe its use and investigate changes in the pattern of use over time. Methods: Secondary analyses of data from all National Health Service funded CP EC consultations in Wales between 1 August 2012 and 31 July 2017 (n=181 359). Data comprised standardised clinical and demographic information, in the form of predefined service user responses, submitted for reimbursement by CPs. Results: Overall service provision remained relatively consistent over the study period, with women aged between 13 and 59 years accessing the service. An association was observed between the time since unprotected sexual intercourse and the day on which the service was accessed (Χ 2 (18)=16 292.327, p<0.001). Almost half (47.9%) of requests were because no contraception had been used, with a strong and positive association for teenagers and women aged 40+ years. A statistically significant and increasing percentage of consultations were accompanied by further sexual health advice (r=0.7, p<0.01). Conclusions: Access to EC through CPs is contributing to reducing teenage conceptions and termination rates. However, action is needed to increase contraception use in all age groups. Reduced availability of CP services on Sundays is a barrier to timely EC access. Findings support an expanded role for community pharmacists in provision of regular contraception.